Overview of risk factors for the incidence of diabetes mellitus in grades 2-4 in Tasikmadu 1 State Elementary School, Malang City - Masfi`ah, Titin; Astuti, Erlina Suci (Institute of Computer Science (IOCS), 2025)
The increasing prevalence of Diabetes Mellitus (DM) in children is an urgent global health issue, along with changes in the lifestyle of elementary school-age children who tend to be sedentary and have unhealthy diets. This study aims to find out the overview and analyze the risk factors for DM incidence in grades 2–4 at SDN Tasikmadu 1 Malang City. The design of this study is descriptive quantitative with data collection techniques through Food Frequency Questionnaire (FFQ), PAQ-C for physical activity, and FINDRISC scores, as well as BMI measurements in 100 respondents. The results showed that 57% of students were obese, 44% often ate fast food and high in sugar, and 100% had screen time >2 hours per day. The physical activity carried out tends to be irregular and lacks intensity. This study concluded that unhealthy diet, sedentary lifestyle, and over-nutrition status were dominant factors in increasing the risk of type 2 DM in children. These findings emphasize the importance of school-based interventions and parental involvement in creating an environment that supports a child's healthy lifestyle. Furthermore, the results provide an evidence-based foundation for integrating early screening using the FINDRISC tool into school health programs. Such integration, when combined with targeted nutrition and physical activity interventions, has the potential to reduce the long-term incidence of type 2 DM among children, particularly in urban areas such as Malang. Further research is recommended using analytical methods and clinical measurements to strengthen the validity of the results.